Certainty and Overconfidence in Future Preferences for Food - Linda Thunström; Jonas Nordström; Jason F. Shogren (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2015)
We examine consumer certainty of future preferences and overconfidence in predicting future preferences. We explore how preference certainty and overconfidence impact the option value to revise today's decisions in the future. We design a laboratory experiment that creates a controlled choice environment, in which a subject's choice set (over food snacks) is known and constant over time, and the time frame is short – subjects make choices for themselves today, and for one to two weeks ahead. Our results suggest that even for such a seemingly straightforward choice task, only 45 percent of subjects can predict future choices accurately, while stated certainty of future preferences (one and two weeks ahead) is around 80 percent. We define overconfidence in predicting future preferences as: the difference between actual accuracy at predicting future choices and stated certainty of future preferences. Our results suggest strong evidence of overconfidence. We find that overconfidence increases with the level of stated certainty of future preferences. Finally, we observe that the option value people attach to future choice flexibility decreases with overconfidence. Overconfidence in future preferences affects economic welfare because it says people have too much incentive to lock themselves into future suboptimal decisions.
Keywords: D03; D12; D83; D90; 330; Choice flexibility; Preference uncertainty; Overconfidence; Sub-optimal decisions; Food